A Hybrid Mesh Routing protocol for ubiquitous internet connectivity in hierarchical Wireless Mesh Networks. (14th March 2011) - Park, Bok-Nyong; Kwon, June-Hyuk
We propose a cross-layer-aware Hybrid Mesh Routing (HMR) protocol for the ubiquitous Internet connectivity in hierarchical Wireless Mesh Networks (WMNs) that can provide the Internet access for users by mesh routers. The HMR protocol applies two independent routing metrics to obtain high performance. The HMR is able to take advantage of each of those protocols strengths depending on the situation, and more suitable than other protocols in hierarchical hybrid WMNs by providing the benefits of both hop count and link quality metrics. Through simulations, we show that our schemes perform better than existing mechanisms in terms of various performance measures.